2020
DOI: 10.1136/bmjopen-2019-031672
|View full text |Cite
|
Sign up to set email alerts
|

Using structural and functional MRI as a neuroimaging technique to investigate chronic fatigue syndrome/myalgic encephalopathy: a systematic review

Abstract: ObjectiveThis systematic review aims to synthesise and evaluate structural MRI (sMRI) and functional MRI (fMRI) studies in chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME).MethodsWe systematically searched Medline and Ovid and included articles from 1991 (date of Oxford diagnostic criteria for CFS/ME) to first April 2019. Studies were selected by predefined inclusion and exclusion criteria. Two reviewers independently reviewed the titles and abstracts to determine articles for inclusion, full text a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 82 publications
(182 reference statements)
1
15
0
Order By: Relevance
“…Moreover, levels of both general and mental fatigue in ME/CFS have been inversely correlated with basal ganglia activation as assessed by fMRI, potentially secondary to dopaminergic deficits (Miller et al, 2014). Numerous other neuroimaging studies also support this notion (see (Almutairi et al, 2020;Cook et al, 2017;Gay et al, 2016;Josev et al, 2019;Manca et al, 2021;Shan et al, 2020;Shan et al, 2018;Tanaka et al, 2006;Van Der Schaaf et al, 2018, 2017Wortinger et al, 2017;Wortinger et al, 2016)). Furthermore, Carandini et al (2021) found an inverse correlation between levels of mental fatigue and DA tract abnormalities in MS. Carandini et al (2021) suggested that this is evidence of dopaminergic abnormalities underlying mental fatigue, as hypothesised by Dobryakova et al (2015).…”
Section: Dopaminementioning
confidence: 88%
“…Moreover, levels of both general and mental fatigue in ME/CFS have been inversely correlated with basal ganglia activation as assessed by fMRI, potentially secondary to dopaminergic deficits (Miller et al, 2014). Numerous other neuroimaging studies also support this notion (see (Almutairi et al, 2020;Cook et al, 2017;Gay et al, 2016;Josev et al, 2019;Manca et al, 2021;Shan et al, 2020;Shan et al, 2018;Tanaka et al, 2006;Van Der Schaaf et al, 2018, 2017Wortinger et al, 2017;Wortinger et al, 2016)). Furthermore, Carandini et al (2021) found an inverse correlation between levels of mental fatigue and DA tract abnormalities in MS. Carandini et al (2021) suggested that this is evidence of dopaminergic abnormalities underlying mental fatigue, as hypothesised by Dobryakova et al (2015).…”
Section: Dopaminementioning
confidence: 88%
“…Researches on the biomarkers of CFS have revealed that the disorder in neuro-immuno-endocrinological pattern is part of the pathophysiological mechanisms [30,31], and functional (non-structural) changes in the brain are found by structural and functional MRI [17], but all of them can't fully reveal a CFS-speci c measure. The research efforts are still made to seek biomarkers or new technology to aid aetiological understanding and treatment options for CFS.…”
Section: Discussionmentioning
confidence: 99%
“…So far, CFS trials into the e cacy and safety of therapies have employed the self-reported subjective measurements as the outcome assessments for evaluating subjective physical function, anxiety, depression, and pain improvement, such as the Chalder Fatigue Scale, Short Form 36 Health Survey Questionnaire (SF-36), Anxiety and Depression Scale and visual analogue pain rating scale [15]. In addition, biological markers and imaging techniques such as MRI are also used to aid clinical diagnoses and effect assessments [16,17]. In this trial, we try to use the Thermal Texture Maps (TTM)─a thermography technique of evaluating thermal signatures of the body through holistic interpretation of infrared images to aid CFS diagnosis and moxibustion dose-effect assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using brain imaging in humans confirm that the within-network connectivity of the SN is weakened in the case of chronic fatigue syndrome/myalgic encephalomyelitis and depression ( 61 – 66 ). In addition, these disorders are associated with persistent weakened connectivity between the SN and CEN and persistent strengthened connectivity between the SN and DMN ( 66 – 68 ).…”
Section: Brain Network and Functional Connectivity In Chronic Fatiguementioning
confidence: 96%